Probiotics in the prevention of dental caries - Johany Duque de Estrada Riverón; Ileana Hidalgo-Gato Fuentes; Yensi Díaz Martell (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
Probiotics have the potential to provide significant benefits to human health, so we decided to investigate the probiotics species that may have preventive action against dental caries mainly in children in order to determine if there can be created a preventive medicine, made from probiotics found in the oral cavity. Oral probiotics that have shown promising activities in the prevention of dental caries are: Streptococcus salivarius (strain K12), BGH01 Lactobacillus salivarius, BGH089 gasseri Lactobacillus, Streptococcus sanguinis and Streptococcus oligofermentans. In vitro studies on the use of probiotics for the prevention of dental caries have shown interesting results, but in vivo they are not very encouraging. It is necessary to deepen in the therapeutic effects of probiotics strains already discovered in order to obtain from them an effective preventive agent against dental caries and so ensuring a better quality of life, especially in children.